There is the possibility of Simichaur becoming Markai Chaur: My experiences in crossing maize species - Basnet, Lal Kumari (CGIAR Systemwide Program on Participatory Research and Gender Analysis for Technology Development and Institutional Innovation, 2001)
A maize farmer describes her experiences learning and using new technologies to improving Her maize crop.